Yeast fermented alcoholic fruit beverages: A systematic review - He, Wenjia; Dong, Tiantian; Zhang, Yiwei; Kortesniemi, Maaria; Liu, Shuxun; Ding, Yuting; Zhou, Xuxia; Laaksonen, Oskar; Yang, Baoru (Elsevier, 2026)
Yeast-driven alcoholic fermentation is widely applied to process fruits into value-added beverages. Fruit genotypes, yeast strains, and beverage production methods significantly influence the diversity and quality of alcoholic beverages. Traditionally, Saccharomyces cerevisiae is regarded as the most commercially important yeast in the alcoholic beverage production markets, whereas other Saccharomyces and non-Saccharomyces is considered to be either harmful or useless. However, the interest of applying these yeasts in numerous innovative yeast fermented alcoholic fruit-based beverages is growing due to their advantageous flavor attributions. In this review, the strategies for enhancing volatile properties and aroma and flavor complexity of alcoholic beverage fermentation were critically examined with a special emphasis on fruit types and yeast strains, as well as their impacts on the quality of alcoholic beverages. The current challenges and future prospects were also discussed on the development of desirable alcoholic beverage production.